Counterflow heat exchanger with core and plenums at both ends. (August 2016) - Bejan, A.; Alalaimi, M.; Lorente, S.; Sabau, A.S.; Klett, J.W.
Abstract : Graphical abstract: Highlights: Architecture: two plenums and core (counterflow) between them. Two-objective design: low flow resistance and low thermal resistance. The two resistances are the lowest when the core is absent. These conclusions hold for laminar and turbulent flow. Abstract: This paper illustrates the morphing of flow architecture toward greater performance in a counterflow heat exchanger. The architecture consists of two plenums with a core of counterflow channels between them. Each stream enters one plenum and then flows in a channel that travels the core and crosses the second plenum. The volume of the heat exchanger is fixed while the volume fraction occupied by each plenum is variable. Performance is driven by two objectives, simultaneously: low flow resistance and low thermal resistance. The analytical and numerical results show that the overall flow resistance is the lowest when the core is absent, and each plenum occupies half of the available volume and is oriented in counterflow with the other plenum. In this configuration, the thermal resistance also reaches its lowest value. These conclusions hold for fully developed laminar flow and turbulent flow through the core. The curve for effectiveness vs number of heat transfer units ( N tu ) is steeper (when N tu  < 1) than the classical curves for counterflow and crossflow.